Evaluation of Serum and Salivary Iron and Ferritin Levels in Children with Dental Caries: A Meta-Analysis and Trial Sequential Analysis - Roohollah Sharifi; Mohammad Farid Tabarzadi; Parsia Choubsaz; Masoud Sadeghi; Jyothi Tadakamadla; Serge Brand; Dena Sadeghi-Bahmani (MDPI AG, 2021)
Background and objective: Dental caries appears to be related to iron deficiency anemia and to low ferritin levels. In the present meta-analysis, we report salivary and serum iron and ferritin levels in children with dental caries, compared to healthy controls. Materials and methods: We searched in Web of Science, Cochrane Library, Scopus, and PubMed/Medline databases to extract studies published until 25 July 2021. We calculated mean differences (MD) and 95% confidence intervals (CI) of salivary and serum iron and ferritin levels in children with dental caries, always compared to healthy controls. In addition, we applied a trial sequential analysis (TSA). Results: A total of twelve articles covering thirteen studies were included in the meta-analysis. The pooled MD for salivary iron level was −5.76 µg/dL (p = 0.57), and −27.70 µg/dL (p < 0.00001) for serum iron level: compared to healthy controls, children with dental caries did not show different salivary iron levels, while children with caries had significantly lower serum iron levels. The pooled MD of salivary ferritin level was 34.84 µg/dL (p = 0.28), and the pooled MD of serum ferritin level was −8.95 µg/L (p = 0.04): compared to healthy controls, children with dental caries did not have different salivary iron levels, but significantly lower serum ferritin levels. Conclusions: The findings of the present meta-analysis showed that salivary levels of iron and ferritin did not differ between children with and without caries, though compared to healthy controls, children with caries had significantly lower salivary and serum iron and ferritin levels. The results are of practical and clinical importance: Possibly, iron and ferritin supplementation might prevent or attenuate dental caries in children at risk. Further, children with caries might suffer from further iron- and ferritin-related health issues. Lastly, serum blood samples, but not saliva samples inform accurately about the current iron and ferritin concentrations in children with or without caries.